2021
DOI: 10.1016/j.ajpc.2021.100199
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect over 3 years by pictorial information to patients and their physician about subclinical atherosclerosis and cardiovascular risk: Results from the VIPVIZA randomized clinical trial

Abstract: Highlights VIPVIZA is a pragmatic randomized controlled trial performed within the regular primary health care and targeting both individuals and physicians. Beneficial effects on risk for cardiovascular disease regardless of sex and education level 3 years after providing pictorial information of subclinical atherosclerosis in addition to regular preventive information. The results indicate that the intervention effect is a combined effect of pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
(35 reference statements)
4
26
0
1
Order By: Relevance
“…Previously, this was shown for VIPVIZA in a 1-year follow-up and lately in a 3-year follow-up. 1 , 4 In the present study, a significant intervention effect was shown in the intervention group and the control group after single-arm cross-over. Conveying risk as pictorial presentation to participants and their respective physician in primary care, and in addition, a follow-up call to the participants tripled the average intensity for initiation of statins during the first 3 years in the intervention group.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previously, this was shown for VIPVIZA in a 1-year follow-up and lately in a 3-year follow-up. 1 , 4 In the present study, a significant intervention effect was shown in the intervention group and the control group after single-arm cross-over. Conveying risk as pictorial presentation to participants and their respective physician in primary care, and in addition, a follow-up call to the participants tripled the average intensity for initiation of statins during the first 3 years in the intervention group.…”
Section: Discussionsupporting
confidence: 55%
“… 5 The compiled information from VIPVIZA makes the indications for treatment more accessible for both physicians and participants, making it more likely to seek consultation of physician from the participants side and easier for the physician to access and communicate the indication for treatment. 4 , 5 , 8 At the same time, a higher propensity among physicians to prescribe statins to these asymptomatic participants over time may also be due to a shift in the healthcare professionals’ attitude towards the treatment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty studies ( 10 , 12 , 22 34 , 36 40 ) met the inclusion criteria by providing vascular images to motivate changes toward improving diet, physical activity or anthropometric measures. Of these, thirteen were observational studies ( 22 34 ) and 7 were RCTs ( 10 , 12 , 36 40 ). Nineteen articles were published within 2006 to 2021, while one study was published in 1996 ( Tables 2 , 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…New strategies are warranted to further encourage a healthier diet and lifestyle, aiming at improving heart health, and provision of vascular health may further encourage these changes. High quality evidence from large randomized controlled trials (RCTs) and meta-analyses has shown that provision of vascular imaging can increase behavior change resulting in improved medication adherence in the long term ( 10 – 12 ), highlighting its potential utility as a promising approach to elicit diet and physical activity change. This is because people are more likely to make healthy changes if they perceive they are at risk of developing a disease and that the condition can lead to serious consequences ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Согласно существующим клиническим рекомендациям, выявление атеросклеротических бляшек в сонной артерии у асимптомного в отношении ССЗ пациента с исходно низким или умеренным ССР по шкалам-рискометрам позволяет провести реклассификацию величины риска и, следовательно, пересмотреть целевые уровни показателей липидного спектра с назначением в большинстве случаев гиполипидемической терапии [2, 3]. Кроме того, визуализация СКА может способствовать формированию более высокой приверженности пациента к выполнению рекомендаций по соблюдению здорового образа жизни и приему лекарственных препаратов [23].…”
Section: Discussionunclassified